2021
DOI: 10.1039/d1ra02663a
|View full text |Cite
|
Sign up to set email alerts
|

Design, step-economical diversity-oriented synthesis of an N-heterocyclic library containing a pyrimidine moiety: discovery of novel potential herbicidal agents

Abstract: A diverse library of pyrimidine–N-heterocycle hybrids was developed through a step-economical diversity-oriented synthesis strategy. In vivo biological screening showed some derivatives exhibited significant potential herbicidal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Final evaluation was performed within 21 days of treatment by visual rating scales of 0–100%. The remaining conditions were set in accordance with the methodology described in the literature [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Final evaluation was performed within 21 days of treatment by visual rating scales of 0–100%. The remaining conditions were set in accordance with the methodology described in the literature [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The structures were confirmed by 1 H NMR, 13 C NMR, 19 F NMR, and HRMS. Pyrimidine compounds have demonstrated a diverse range of biological activities in previous studies, encompassing antiviral, antibacterial, fungicidal, insecticidal, and herbicidal properties [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Consequently, a variety of pyrimidine derivatives (Figure 1) have been successfully developed into commercial pesticides that have made significant contributions to the smooth functioning of agricultural production.…”
Section: Chemistrymentioning
confidence: 99%
“…Molecules 2023, 28, 6498 2 of 13 herbicidal properties [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Consequently, a variety of pyrimidine derivatives (Figure 1) have been successfully developed into commercial pesticides that have made significant contributions to the smooth functioning of agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…24 Previously, we have also found that compounds bearing the pyrimidinyloxybenzyl scaffold show consistent postemergence herbicidal activity against Digitaria sanguinalis. 25 Their herbicidal spectrum could be tuned with diverse substituents and motifs, among which the compound containing hydrophobic tetrahydrocarbazole motif (Figure 1a) showed the highest and broadest weed control efficiency. Diaryl ether is a versatile scaffold widespread in numerous natural products, 26 agrochemicals, 27 and pharmaceuticals.…”
Section: ■ Introductionmentioning
confidence: 99%